(untitled) (Ocean and Coastal Research, 2021)
Oceanic islands are important areas of environmental, social, economic, and scientific interest. Therefore, it is essential to identify pollutants in these environments, including large (1 mm to ≤ 5 mm) and small microplastics (SMP) (1 μm to ≤ 1 mm). Here, SMP were identified and characterized in the windward (WW) and leeward (LW) beaches of Fernando de Noronha Island. Samples were collected from 900 cm2 quadrants on the strandline of 15 sandy beaches and were sieved through stainless steel sieves with 1 mm mesh. The SMP were characterized according to their shape, colour, and size. Synthetic fibres and fragments were identified, and synthetic fibres were predominant. Statistical differences were not found between the WW and LW beaches (160.0±137.5 particles m-2 and 128.0±84.3 particles m-2, respectively; Mann-Whitney U test: U=198.5; p=0.81) in relation to the total amount of SMP deposited on the beaches. Also, both types/ shapes were present in the two groups of beaches (Friedman’s test, X2 r=6.09; p=0.91). The environmental forcings controlling the transport and potential deposition of synthetic fibres may have been different from those acting on fragments that more resembled the grains of sand in the beaches. Although it is difficult to prevent allochthonous sources of SMP at the small scale, management actions on the island are mandatory to prevent autochthonous sources.